Making a Turtle Conservation Website and Sumbreng Sea Pearl Education Tour for Ecosystem Balance - Anggara Trisna Nugraha; utomo, Devina Puspita Sari; utomo, Diego Ilham Yoga Agna; utomo, Salsabila Ika Yuniza; Riyadi, Faris; Rahmat Adzani, Fajar; utomo, Andika Aldo Pratama; utomo, Rahmania Firdiansyah (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
The coast is an area that has the potential to be used as a tourist spot, including for turtle conservation which is relied on as an economic support. Turtles are one of the animals protected by law. Not only are they protected by law because it is feared that they will eventually become extinct, but in marine ecosystems turtles also have their own benefits. The Turtle Conservation